Acute ischemic stroke after cardiac catheterization: the protamine low-dose recombinant tissue plasminogen activator pathway. Issue 3 (April 2017) - Guevara, Carlos; Quijada, Alonso; Rosas, Carolina; Bulatova, Katya; Lara, Hugo; Nieto, Elena; Morales, Marcelo
Abstract : N/A: Intravenous thrombolysis is the preferred treatment for acute ischemic stroke; however, it remains unestablished in the area of cardiac catheterization. We report three patients with acute ischemic stroke after cardiac catheterization. After reversing the anticoagulant effect of unfractionated heparin with protamine, all of the patients were successfully off-label thrombolyzed with reduced doses of intravenous recombinant tissue plasminogen activator (0.6 mg/kg). This dose was preferred to reduce the risk of symptomatic cerebral or systemic bleeding. The sequential pathway of protamine recombinant tissue plasminogen activator at reduced doses may be safer for reducing intracranial or systemic bleeding events, whereas remaining efficacious for the treatment of acute ischemic stroke after cardiac catheterization.